Luminescent Lanthanoid Calixarene Complexes and Materials - Massi, Massimiliano; Ogden, Mark (mdpi, 2017)
This review aims to provide an overview of recent examples of lanthanoid-calixarene complexes incorporated into light-emitting materials. Background information on the antenna effect and early work on lanthanoid complexes on calixarenes is provided to set the context. Classes of materials discussed include polymers, nanoparticles, and metal clusters.